JOAQUIM NORBERTO E SUA CONTRIBUIÇÃO À EDIÇÃO DE TEXTOS E À CRÍTICA LITERÁRIA - Roberto Acízelo de Souza (Fólio, 2009)
In Joaquim Norberto’s broad and heterogeneous works the texts editions hold an outstanding position. Literary criticism, in its turn, appears as an activity derived from that one, as well as in a lower status in the whole of his production. As a critic, he follows mainly a biographic orientation, frequently trimming the reconstitution of the studied writers’ lives with episodes worthy of sentimental feuilletons.